PENERAPAN PENDEKATAN MATEMATIKA REALISTIK PADA PEMBELAJARAN MATEMATIKA DI KELAS VII SMP NEGERI 1 MERANGIN - Yohanes (Pendidikan Matematika | STKIP YM Bangko, 2018)
The purpose of this study is to find out the mathematics learning outcomes of students using a realistic approach is higher than using conventional learning. The research method used is the experimental research method. The population in this study were Grade VII Students of SMP Negeri 1 Merangin, while the sample used in this study was VIIB class as the experimental class and VIID class as the control class. Data collection uses a questionnaire method with a Likert scale to motivate students, while the problem-solving ability with essay questions. The data analysis method for motivation with the t-test, for test analysis is by the t-test, before carrying out the t-test on the similarity of the two averages, the normality test and the homogeneity test first. Then the hypothesis test aims to find out whether the hypothesis is accepted or rejected. Hypothesis testing is done using the z-test. The results of the research data analysis show for learning motivation of class VII students of SMP Negeri 1 Merangin in following mathematics learning after using a realistic mathematical approach better than motivation to learn mathematics before using this realistic mathematical approach with an average initial motivation of 2.38 and final motivation of 3.08. Whereas the mathematical problem solving abilities of class VII students at SMP Negeri 1 Merangin using a realistic mathematical approach were higher than conventional mathematics learning outcomes with an experimental class average of 80.46 and a control class of 57.79. Keywords: Realistic Mathematical Approach, Learning Motivation, and Mathematical Problem Solving Ability